Improved Sensitivity of Dual-Axis Micro-Mechanical Probe for Friction Force Microscope - Hiroaki Amakawa (Japanese Society of Tribologists, 2008)
Improvement of the sensitivity of a dual-axis probe for friction force microscopy is presented. The dual-axis micro-mechanical probe combines a double cantilever and torsion beams. This probe could reduce the mechanical cross-talk between the lateral and vertical force detections. In addition, dual-axis forces can be detected by measuring the dual-axis displacement of the probe end using the optical lever-based method. A low reflection region is formed at the probe end. The region is irradiated with an optical lever laser light and the reflected light is focused onto a four-segmented photo diode (PD). The lateral force can be detected by measuring the displacement of the probe end using the dark region displacement on PD. A shallow step structure was used as a low reflection region in our previous study. However, its darkness was not enough and the improvement of the sensitivity was difficult. In this paper, a new type of low reflection region is presented. The low reflection region using a slope-structure could improve the lateral deflection sensitivity by a factor of 1.4 as compared with conventional one. And the minimum detection limits of the lateral deflection and force were of the order of 1 nm and 1 nN, respectively. This leads to accurate investigation of nanotribological phenomena.